2011
DOI: 10.1007/s00018-011-0787-2
|View full text |Cite
|
Sign up to set email alerts
|

MICALs in control of the cytoskeleton, exocytosis, and cell death

Abstract: MICALs form an evolutionary conserved family of multidomain signal transduction proteins characterized by a flavoprotein monooxygenase domain. MICALs are being implicated in the regulation of an increasing number of molecular and cellular processes including cytoskeletal dynamics and intracellular trafficking. Intriguingly, some of these effects are dependent on the MICAL monooxygenase enzyme and redox signaling, while other functions rely on other parts of the MICAL protein. Recent breakthroughs in our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 92 publications
1
53
0
Order By: Relevance
“…Semaphorins are known to control neuronal differentiation through various signaling pathways (Pasterkamp, 2012) and, intriguingly, both Ndr1 and Ndr2 have been shown to interact with MICAL-1 (molecule interacting with CasL-1), an enzyme that links semaphorins to F-actin rearrangement during axonal and dendritic growth. MICAL-1 inhibits Ndr1/2 by competing with Mst kinases for binding at the hydrophobic motif and it has been suggested that semaphorins may disinhibit the kinase by sequestering MICAL (Hung et al, 2010;Zhou et al, 2011). Ndr kinases and semaphorins thus seem to interact in the intracellular signaling pathways that lead to ␤1-integrin activation in differentiating neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Semaphorins are known to control neuronal differentiation through various signaling pathways (Pasterkamp, 2012) and, intriguingly, both Ndr1 and Ndr2 have been shown to interact with MICAL-1 (molecule interacting with CasL-1), an enzyme that links semaphorins to F-actin rearrangement during axonal and dendritic growth. MICAL-1 inhibits Ndr1/2 by competing with Mst kinases for binding at the hydrophobic motif and it has been suggested that semaphorins may disinhibit the kinase by sequestering MICAL (Hung et al, 2010;Zhou et al, 2011). Ndr kinases and semaphorins thus seem to interact in the intracellular signaling pathways that lead to ␤1-integrin activation in differentiating neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mical2 was found to localize to the nucleus. In humans and mice, Mical1 and Mical3 are detected in tissues such as brain, lung, spleen, and kidney (41,71), but they appear to be expressed in other tissues as well. The presence of different Micals in different cell types and compartments further highlights the diverse in vivo functions of this family of enzymes.…”
Section: Stereospecific Regulation Of Meto By Selenoprotein Msrb1mentioning
confidence: 99%
“…Human MICAL proteins have four conserved domains: an N-terminal flavin adenine dinucleotide (FAD) binding domain, a calponin homology (CH) domain, a Lin11, Isl-1 and Mec-3 (LIM) domain and a C-terminal coiled-coil (CC) domain (Fig. 1A) (reviewed by Hung and Terman, 2011;Zhou et al, 2011a). MICAL1 has the most closely related domain architecture to Drosophila MICAL, whereas MICAL3 displays the least homology (Fig.…”
Section: Introductionmentioning
confidence: 99%